Taxing Pensions and Retirement Benefits in Germany - Axel Börsch-Supan; Christopher Quinn (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper motivates and describes the tax treatment of German retirement benefits and pensions after the 2005 reform initiated by the German Federal Constitutional Court. The main question is whether this reform has produced a “level playing field” among the many instruments generating retirement income in Germany. The paper briefly outlines rational principles for the taxation of retirement benefits and pensions and compares these with current practice in Germany and abroad.
Keywords: 330